2024
DOI: 10.1037/amp0001209
|View full text |Cite
|
Sign up to set email alerts
|

We built this culture (so we can change it): Seven principles for intentional culture change.

MarYam G. Hamedani,
Hazel Rose Markus,
Rebecca C. Hetey
et al.

Abstract: Calls for culture change abound. Headlines regularly feature calls to change the "broken" or "toxic" cultures of institutions and organizations, and people debate which norms and practices across society are now defunct. As people blame current societal problems on culture, the proposed fix is "culture change." But what is culture change? How does it work? Can it be effective? This article presents a novel social psychological framework for intentional culture change-actively and deliberately modifying the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 131 publications
0
1
0
Order By: Relevance
“…As a comprehensive culture change effort using the CCF, the research reported here yields several notable theoretical advances. Consistent with past theorizing ( 44 46 ), our findings suggest that initiating culture change using the CCF is both viable and effective in educational contexts ( 47 ). While past research has illustrated isolated effects between particular levels of the CCF ( 38 , 51 – 53 , 60 ), the current research demonstrated both causal and correlational effects across all levels, demonstrating the possibility of initiating cascading change through targeted action.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As a comprehensive culture change effort using the CCF, the research reported here yields several notable theoretical advances. Consistent with past theorizing ( 44 46 ), our findings suggest that initiating culture change using the CCF is both viable and effective in educational contexts ( 47 ). While past research has illustrated isolated effects between particular levels of the CCF ( 38 , 51 – 53 , 60 ), the current research demonstrated both causal and correlational effects across all levels, demonstrating the possibility of initiating cascading change through targeted action.…”
Section: Discussionsupporting
confidence: 88%
“…In any context, culture change is an ambitious goal ( 47 ). Yet, the persistent racial and socioeconomic disparities that span all aspects of education make the necessity of educational culture change readily apparent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…People learn social structures and subsequently reenact or challenge them, in the process reinforcing or changing the larger social structure. Changing a social structure, thus, requires changing individuals (See Hamedani et al, 2023;Madva et al, 2023;Skinner-Dorkenoo et al, 2023, for similar perspectives.). Structural reforms, like policies, programs, or laws, require individual buy-in.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%